Probabilistic risk assessment applied to biological growth on external surfaces with ETICS - Nuno M. M. Ramos (2013)
External thermal insulation composite systems (ETICS) for walls are a very interesting technology but, despite its thermal advantages, ETICS is faced with a very serious problem: The defacement caused by biological growth. At this moment, no simple process has yet been developed to predict the risk of ETICS defacement, which may be used by designers, engineers and the building industry. A methodology of probabilistic risk assessment of biological growth on ETICS exterior layer will provide guidelines to help in decision. In this work, a risk analysis approach has been improved and evaluated in a case study with ETICS. The scope of the risk analysis was established to define its main purposes when applied to ETICS. Secondly, a qualitative probabilistic analysis was done to determine the variables and parameters that are mandatory in ETICS defacement and should be considered in the risk analysis. Data regarding the mandatory variables and parameters in ETICS defacement was collected in order to establish a probabilistic approach of its variation and, a quantitative probabilistic risk analysis strategy is presented based in Monte Carlo simulations. Finally, a meta-model, Response Surface Methodology, was developed and compared with a hygrothermal simulation tools, for assessing biological growth on ETICS as a function of exterior temperature, exterior relative humidity and atmospheric radiation. Response Surface Methodology is one of the most widely-used metamodels, which refers not simply to the use of a response surface as a multivariate function but also to the process for determining the polynomial coefficients themselves. Copyright (c) 2011 by IPAC'11/EPS-AG.